Neuroprotection by Ozanimod Following Intracerebral Hemorrhage in Mice - Wang, Fei; Zhang, Xiangyu; Liu, Yang; Li, Zhe; Wei, Ruixue; Zhang, Yan; Zhang, Ruiyi; Khan, Suliman; Yong, V. Wee; Xue, Mengzhou (Frontiers in Molecular Neuroscience, 2022)
The destruction of the blood-brain barrier (BBB) after intracerebral hemorrhage (ICH) is associated with poor prognosis. Immunomodulation of Sphingosine 1-phosphate receptor (S1PR) can improve the outcomes of ICH. Ozanimod (RPC-1063) is a newly developed S1PR regulator which can selectively modulate type 1/5 sphingosine receptors. Here, we studied the impact of Ozanimod on neuroprotection in an experimental mouse model of ICH, induced by injecting collagenase type VII into basal ganglia. In our current study, ozanimod was administered by gavage 2 hours after surgery and once a day thereafter until sacrifice. Our study demonstrated that Ozanimod treatment improved neurobehavioral deficits in mice and decreased the weight loss after ICH. Ozanimod significantly reduced activated microglia and neutrophils infiltrated in the perihematoma region. Furthermore, Ozanimod reduced the hematoma volume and the water content of the brain. Moreover, the results of TUNEL staining indicated that Ozanimod mitigated brain cell death. The quantitative data of Evans blue (EB) staining showed that Ozanimod reduced EB dye leakage. Overall, we report that ozanimod can reduce the destruction of BBB and exert a neuroprotective role following ICH in mice.